Tradisi Terkait Upacara Kehamilan Dan Kelahiran Pada Suku Jawa Di Desa Rintis - Fitri Amja Yani (Universitas Dehasen Bengkulu, 2023)
Indonesia is an archipelagic country with various traditions and ways of life. Cultural rituals during pregnancy and childbirth are customs and habits that are practiced in many places. Rintis Village is one of the villages that practices pregnancy and childbirth ceremonies for the Javanese people. This study aims to describe the process of a series of ceremonies from pregnancy to childbirth. In this study using qualitative methods, the method of collecting data by means of participatory observation, and in-depth interviews. In this study, several things were found, namely (1) Traditional pregnancy ceremonies such as telonan and tingkeban. (2) Postpartum traditional ceremonies, namely brokohan, sepasaran and selapanan. (3) There is also a tradition of gebrak bayen and baby roosters. (4) There is a symbolic meaning of offerings and offerings contained in a series of pregnancy and postpartum ceremonies. Basically, all customs and rituals are adhered to and carried out only with the hope of receiving God's forgiveness. In addition, maintaining ancestral traditions and upholding balance and satisfaction in life, namely a safe environment free from disturbances caused by other living things or the natural environment.